Peningkatan Kesadaran Hukum Masyarakat Desa Serangkat Melalui Edukasi Interaktif Mengenai Bantuan Hukum - Luthfiana Rihadatul ‘Aisy; Eksa Rusdiyana; Sudibya Sudibya; Dinda Dwi Prasetiyani; Dinda Putri Permatasari; Alit Adi Saputra; Muhammad Ezzat Alfauzi; Moh Sayful Zuhri; Muhamad Najib Shofy (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Legal awareness plays a crucial role in law enforcement, especially in remote areas like Serangkat Village. The government has a direct responsibility to support the community there. The lack of legal awareness in Serangkat Village is due to the community's tendency to resolve legal issues based on local customary law, a lack of trust in law enforcement authorities, and concerns about significant financial consequences. The primary goal of this activity is to enhance understanding of the importance of legal awareness and introduce the Legal Aid program organized by the government for the community. This research uses a qualitative descriptive analysis method supported by field observations, planning, and implementation of activities. Legal Aid refers to free legal services provided by authorized institutions to individuals in need. The program aims to protect the constitutional rights of individuals and promote social changes that are fair. The results of this awareness campaign are evident through the community's understanding of the urgency of legal awareness and the availability of the Legal Aid Program provided by the government